Discovery of the first potent proteolysis targeting chimera (PROTAC) degrader of indoleamine 2,3-dioxygenase 1 - Mingxing Hu; Weilin Zhou; Yijie Wang; Dongping Yao; Tinghong Ye; Yuqin Yao; Bin Chen; Gongping Liu; Xifei Yang; Wei Wang; Yongmei Xie (Elsevier, 2020)
Cancer immunotherapy is revolutionizing oncology and has emerged as a promising strategy for the treatment of multiple cancers. Indoleamine 2,3-dioxygenase 1 (IDO1), an immune checkpoint, plays an important role in tumor immune escape through the regulation of multiple immune cells and has been regarded as an attractive target for cancer immunotherapy. Proteolysis Targeting Chimeras (PROTAC) technology has emerged as a new model for drug research and development for its advantageous mechanism. Herein, we reported the application of PROTAC technology in targeted degradation of IDO1, leading to the discovery of the first IDO1 PROTAC degrader 2c, which induced significant and persistent degradation of IDO1 with maximum degradation (dmax) of 93% in HeLa cells. Western-blot based mechanistic studies indicated that IDO1 was degraded by 2c through the ubiquitin proteasome system (UPS). Label-free real-time cell analysis (RTCA) indicated that 2c moderately improved tumor-killing activity of chimeric antigen receptor-modified T (CAR-T) cells. Collectively, these data provide a new insight for the application of PROTAC technology in tumor immune-related proteins and a promising tool to study the function of IDO1.